CLOUD TECHNOLOGIES AND THEIR ADVANTAGES (Web of Technology: Multidimensional Research Journal, 2025)
This article analyzes the importance of cloud technologies in the context of modern digital transformation and the convenience they create for users. The main types, principles of operation and advantages of cloud computing systems are widely covered. Also, real practical applications are considered on the example of enterprises and the education system. The article reveals the possibilities of effective use of these technologies in the era of developing information technologies.